Juridical analysis of working guarantees of sexual workers in the macro social state of colombian rights - Ardila Rincón, Juan Ricardo; Florez Martinez, Yuli Paola; Asprilla Bolivar , Yulesmi; Ardila Rincón, Juan Ricardo; Florez Martinez, Yuli Paola; Asprilla Bolivar , Yulesmi; Ardila Rincón, Juan Ricardo; Florez Martinez, Yuli Paola; Asprilla Bolivar , Yulesmi (Corporación Universitaria Americana, 2020)
Sexual workers are a population that have been stigmatized through history, not only on social environments but when generating laws, decrees and judicial sentences. That’s why through this applied investigation article focused on the socio-legal searched the regulatory framework that establish working the rights and guarantees of sexual workers in Colombia’s legal system. After the history, regulatory and jurisprudential precedent recap, the struggle to make prostitution working rights valid present positiveresults, every time what was found is that Colombia’s legal system did not have a legal recognition of prostitution as a job and consequently the working rights recognition to who practice this activity. The stigmatized treatment stand out and in some cases degrading to who does this practice, since it has been approach from a prohibitionist focus and mandatory and not since the legalist vision that is the only perspective that recognize this activity as a job.